Ichthyofauna of Alas River, around Soraya Research Station, Leuser Ecosystem Area, Subulussalam, Aceh - Furqan Maghfiriadi; Ilham Zulfahmi; Epa Paujiah; M. Ali Sarong (Jurnal Iktiologi Indonesia, 2019)
The ichthyofaunal study is needed to reveal the diversity of fish, investigate the existence of native and introduced fish, inventory some species that are potential as consumed and ornamental fishes, and to be a part of the effort to find new species. This study aimed to determine the composition of freshwater fish in the Alas River around Soraya Research Station, Leuser Ecosystem Area, Subulussalam, Aceh. Research was conducted from July to September 2018. Fish sampling was carried out at six research stations using selective gill nets, throwing net, hook, tray net, and scoop net. A total of 339 individual’s fish belonging to 20 species, eight families and three orders was collected from sampling location. Cyprinidae was the predominant family found in the Alas River. As many of 16 fish species has the potential as consumption fish. Two introduced fishes were collected, namely tilapia (Oreochromis niloticus) and Amazon sailfin catfish (Pterygoplichthys pardalis). One fish species is thought to have the potential as a new species, i.e. catfish (Hemibagrus sp.). The result of this study can be used as a basic data for policy decision making in order to develop management program of Leuser ecosystem in the future. Abstrak Kajian iktiofauna diperlukan dalam rangka mengungkap keanekaragaman ikan, investigasi keberadaan ikan asli dan ikan asing, inventarisasi jenis-jenis ikan yang berpotensi sebagai ikan konsumsi dan hias, serta menjadi bagian dari upaya menemukan ikan jenis baru. Penelitian ini bertujuan untuk mengkaji komposisi ikan air tawar di Sungai Alas sekitar Stasiun Penelitian Soraya, Kawasan Ekosistem Leuser, Subulussalam, Aceh. Penelitian ini dilakukan mulai Juli hingga September 2018. Pengambilan contoh ikan dilakukan di enam stasiun penelitian dengan menggunakan alat tangkap berupa jaring insang, jala, pancing, serok dan sudu. Sebanyak 339 individu ikan yang tergolong kedalam 20 jenis, delapan famili dan tiga ordo berhasil dikoleksi selama penelitian. Cyprinidae merupakan famili ikan yang paling banyak ditemukan. Enam belas jenis ikan yang dikoleksi berpotensi dijadikan sebagai ikan konsumsi. Ikan asing yang ditemukan berjumlah dua jenis yaitu ikan nila (Oreochromis niloticus) dan ikan sapu-sapu (Pterygoplich-thys pardalis). Terdapat satu jenis ikan yang diduga berpotensi sebagai ikan jenis baru yaitu sing-sing (Hemibagrus sp.). Hasil penelitian ini berpotensi dimanfaatkan sebagai data dasar dalam rangka pengambilan kebijakan pengelo-laan Kawasan Ekosistem Leuser di masa mendatang.